The existence and challenges of consumer dispute settlement agency in Indonesia in globalization era - Kerti, N.G.N. Renti Maharaini (Indonesian Journal of Multidisciplinary Science, 2023)
Globalization has impacted Indonesia's economy, providing consumers with diverse goods and services. Advances in technology have facilitated global transactions, benefiting consumers. However, businesses have benefited from consumers through advertisements and promotions. The Indonesian Consumer Protection Law offers alternative dispute resolution options, including the Consumer Dispute Settlement Agency (BPSK). Despite the existence of alternative institutions, BPSK remains a necessary institution for quick and affordable dispute resolution. Strengthening the agency, achieving budget independence, improving human resources, establishing an online system, and establishing BPSK in each province and second-level region are crucial for its future success.